Jamaica: Development of secondary education - UNESCO (UNESCO)
This report presents the findings and recommendations of a Sector Survey undertaken by the Unesco Secretariat. Chapter 1 provides a succinct summary of the findings of the Survey. Chapter 2 analyses the observed relationship between secondary education as producer of job seekers and the labour market. Chapter 3 presents recommendations aimed at rationalizing secondary education in order to render it more efficient internally and more relevant to the socio-economic development of Jamaica. Chapter 4 deals with the implementation of the proposed rationalization measures. Section A of the Appendix contains an analysis of the socio-economic context within which secondary education should be viewed, while Section B presents the detailed findings of the Survey and their analysis, with each of eight chapters devoted to a specific aspect of secondary education. The Annexes contain the statistical information used for the Report and the Appendix
Keywords: Educational development